Factor Analysis Applied in the Construction of the Socio-Environmental Performance Index (IDRSA) in the Guajará-Mirim Free Trade Area, Brazil / Bolivia Border - Paraguassu-Chaves, Carlos Alberto; Cavalcante, Fabio Robson Casara; Filho, Allan Kardec Duailibe Barros; Almeida, Fabrício Moraes de; Dantas, Lenita Rodrigues Moreira; Macieira, Carlos de Andrade; Neto, João Viana Fonseca; Barata, Charlles da Silva; Siqueira, Sorin Melgar Maciel; Cavalcante, Ana Maria Morais da Fonseca; Netto, Edmundo Machado (International Journal of Advanced Engineering Research and Science, 2020)
Objective: to analyze the socio-environmental responsibility of commercial companies in the wholesale, retail, wholesale-retail and wholesale-retail sectors within the scope of the free trade area of Guajará-Mirim, Rondônia, Brazil / Bolivia border. Method: the Social and Environmental Responsibility Performance Index - IDRSA was calculated according to the Factor Analysis techniques presented by Hair et al 13, Santana 14,15 and Cavalcante 16. A questionnaire (created by Cavalcante and Siqueira 17) was applied to 32 companies in the ALCGM economic sector, based on a set of social, environmental, economic and free question variables. Results:The average of the results found for each of the analyzed parameters (social, environmental and economic) reaches the performance index of socio-environmental responsibility of the companies for each of the economic sectors surveyed in the free trade area of Guajará-Mirim. The wholesale-retail sector had the best performance among all sectors with an index (IDRSA 0.561), considered "regular" performance. The sector of retail and wholesale (IDRSA 0.470) and the retail sector (IDRSA 0.420) also display rankings with regular performance indexes. The wholesale sector (IDRSA 0.374) was classified as “bad”. Final considerations: Although ALCGM emerged from a policy framed in the context of endogenous development theory, motivated by local forces or by interests of strategic economic sectors, benefited by tax incentives, revealed weakness in socio-environmental aspects. What is expected is to contribute so that socio-environmental responsibility is defined and demanded as policies and practices in the companies that make up the ALCGM.